2015 International Conference on Information Society (I-Society) 2015
DOI: 10.1109/i-society.2015.7366859
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating degrees of tenant isolation in multitenancy patterns: A case study of cloud-hosted Version Control System (VCS)

Abstract: Abstract-One of the key concerns of implementing multitenancy (i.e., serving multiple tenants with a single instance of an application) on the cloud is how to enable the required degree of isolation between tenants, so that the required performance of one tenant does not affect other tenants. There is little research which provides empirical evidence on the required degree of isolation between tenants under different cloud deployment conditions. This paper applies COMITRE (COmponent-based approach to Multitena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…They also evaluated the performance of these patterns through a series of experiments and summarize a set of valuable conclusion and best practices on how to design a multi-tenant data model. [18] evaluated the degree of isolation among tenants using a component based approach to multi-tenancy through rerouting. This evaluation followed an empirical studies approach, where they implemented the three identified multitenancy patterns in a multi-tenant component of Hudson's file system.…”
Section: Related Workmentioning
confidence: 99%
“…They also evaluated the performance of these patterns through a series of experiments and summarize a set of valuable conclusion and best practices on how to design a multi-tenant data model. [18] evaluated the degree of isolation among tenants using a component based approach to multi-tenancy through rerouting. This evaluation followed an empirical studies approach, where they implemented the three identified multitenancy patterns in a multi-tenant component of Hudson's file system.…”
Section: Related Workmentioning
confidence: 99%
“…One of the main challenges of implementing multitenancy is how to ensure that there is isolation between tenants (hereafter referred to as multitenancy isolation) sharing components of an application, for example, a cloud-hosted application [1] [2] [3]. As software tools are increasingly being deployed on the cloud for software development, there is need to properly isolate a tenant's code files and processes so that the required performance, resource utilization, and access privileges of one tenant does not affect other tenants.…”
Section: Introductionmentioning
confidence: 99%